2016
DOI: 10.1039/c6tc00681g
|View full text |Cite
|
Sign up to set email alerts
|

Back-contacted hybrid organic–inorganic perovskite solar cells

Abstract: A novel architecture for quasi-interdigitated electrodes (QIDEs) allows for the fabrication of back-contacted perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 28 publications
1
79
0
Order By: Relevance
“…This device configuration, although conceptually interesting, has not yet yielded high efficiencies. The authors reported a backward scan efficiency of 6.5 % and a forward scan of 3.7 %, and therefore high hysteresis (Figure F) …”
Section: Promising Hole Transporter Materials (Htms) Alternatives To mentioning
confidence: 95%
See 1 more Smart Citation
“…This device configuration, although conceptually interesting, has not yet yielded high efficiencies. The authors reported a backward scan efficiency of 6.5 % and a forward scan of 3.7 %, and therefore high hysteresis (Figure F) …”
Section: Promising Hole Transporter Materials (Htms) Alternatives To mentioning
confidence: 95%
“…Thea uthors reported ab ackward scan efficiency of 6.5 %a nd af orward scan of 3.7 %, and therefore high hysteresis ( Figure 3F). [99] Flexible solar cells based on plastic substrates are one of the most appealing applicationsf or perovskite materials as these can be processed at lowt emperatures. [100] Plastic substrates tend to degrade with temperaturesa bove 200 8C.…”
Section: Emergent Substrates:from Ito/fto-free Devices To Flexible Armentioning
confidence: 99%
“…Spatial photocurrent microscopy is a technique which allows localized illumination of a focused laser excitation beam and collection of spatially resolved photocurrent signals simultaneously. The tool is mostly based on a scanning confocal microscopy or scanning near‐field optical microscopy with an auxiliary port . It is vital to understand the photocurrent generation mechanisms, i.e., distinguish photovoltaic mode from the photo‐thermoelectric mode, and determine the role of the light‐sensitive components.…”
Section: Engineering Electronic Structures In 2d Transition Metal Dicmentioning
confidence: 99%
“…Therefore, a change to the state‐of‐the‐art lateral structure in which both the anode and cathode are positioned on the same side and the photoabsorber layer is stacked on top will not just solve these problems but also enhance the flexibility, light absorption, scattering, and reflection to make it rival well‐established solar cell technologies . In lateral OTP devices, both the electrodes are in a juxtaposed orientation and loss through parasitic light absorption is prevented by an exposed surface without a top electrode, so there is no requisite for a transparent electrode and any damage by metal evaporation and abrasion by subsequent layer or device annealing can be averted . Additionally, the possibility of efficient and competent module integration can be accomplished (in parallel or series) by designing interdigitated electrode patterns for the desired current and voltage analogous to silicon solar cells but contrary to the vertical architecture in which isolated individual devices are connected either in series or parallel .…”
Section: Introductionmentioning
confidence: 99%
“…[17] In lateralO TP devices, both the electrodes are in aj uxtaposed orientation and loss through parasitic light absorptioni sp reventedb ya ne xposed surface withoutatop electrode, so there is no requisite for at ransparent electrode and anyd amage by metal evaporation and abrasion by subsequent layer or device annealing can be averted. [18] Additionally, the possibility of efficient and competent module integration can be accomplished (in parallel or series) by designing interdigitated electrode patterns for the desired current and voltage analogoust os ilicon solar cells but contrary to the verticala rchitecture in which isolated individual devices are connected either in series or parallel. [19] Despite such overwhelming attractive features, little work on interdigitated architectures of organic photovoltaics that incorporate 1D self-assembled poly(3-hexylthiophene) nanowires hasb een reported.…”
Section: Introductionmentioning
confidence: 99%